2017
DOI: 10.1111/pde.13335
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in stratum corneum functions between Chinese and Thai infants residing in Bangkok, Thailand

Abstract: Background/Objectives: Ethnic and racial differences in infant skin have not been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…18 Likewise, TEWL on the upper arm (not on the thigh and buttock) were inversely correlated with age in Thai children, not in Chinese, aged 6-24-month old. 19 In contrast, we showed here that TEWL on the shin were positively correlated with age in girls aged >12 months to 3-year old, and boys aged 1 month to 12-month old, in consistent with other study in Chinese…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…18 Likewise, TEWL on the upper arm (not on the thigh and buttock) were inversely correlated with age in Thai children, not in Chinese, aged 6-24-month old. 19 In contrast, we showed here that TEWL on the shin were positively correlated with age in girls aged >12 months to 3-year old, and boys aged 1 month to 12-month old, in consistent with other study in Chinese…”
Section: Discussionsupporting
confidence: 93%
“…The trend of changes in stratum corneum hydration levels was similar to that in TEWL. Previous study demonstrated that stratum corneum hydration levels on the upper arm were lower in 13–24‐month‐old infants than in 2–12‐month‐old infants 19 . Correspondingly, we show here that stratum corneum hydration levels were higher in infants 1–12‐month old than in that over 12‐month old.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A lower NMF and ceramide content was observed in young children compared to adult epidermis [7, 27, 28]. In addition, ethnic variations in SC ceramide levels have been described [29].…”
Section: Biochemical Composition Adaptationmentioning
confidence: 99%